Selected Mollusks from Pujada Bay, Philippines: Heavy Metal Health Risk Assessment and Antibacterial Activities - Tayone, Janeth Cuevas; Ortiz, Jeaneil Camille C; Tayone, Wilanfranco C (Asian Journal of Biological and Life Sciences, 2020)
The study assessed the human health risks of heavy metals and the antibacterial activities of commonly consumed mollusk species,Anadara maculosa, Antigona puerpera, Canarium urceusandLambis lambisfrom Guang-guang, Pujada Bay, City of Mati, Davao Oriental, Philippines. Cadmium (Cd) and lead (Pb) contents were determined using Atomic Absorption Spectrophotometer. On the other hand, the agar well diffusion method was used for the antibacterial activity determination. Water quality, which includes temperature, pH, dissolved oxygen and total dissolved solids, were also investigated. The Cd and Pb concentrations in four marine mollusks were below the standard limit for Cd and Pb in fish and fishery/aquatic products set by the FAO No.210 series of 2001. Furthermore, the result of the human health risk assessment using Chronic Daily Intake, Hazard Quotient and carcinogenic risk for Cd and Pb were below the acceptable level set by the United States Environmental Protection Agency. Cd and Pb metals uptake through marine mollusc ingestion posed no potential non-carcinogenic and carcinogenic risks to human health. On the other hand, the results of the physico-chemical parameters of seawater were within the standard limits set by DAO No. 2016-08 Water Quality Guidelines and General Effluent Standards of 2016, indicating that Guang-guang, Pujada Bay has a good marine water condition. Moreover, onlyC. urceuscrude extract showed antibacterial activity againstStaphylococcus aureusbacteria. Hence, further studies on the content of its natural products are highly recommended.
Keywords: Antibacterial activity; Cadmium; Heavy metals; Lead; Mollusks; Risk Assessment